Structures of Solid‐Electrolyte Interphases and Impacts on Initial‐Stage Lithium Deposition in Pyrrolidinium‐Based Ionic Liquids - He, Jun‐Wu; Gu, Yu; Wang, Wei‐Wei; Wang, Jun‐Hao; Chen, Zhao‐Bin; He, Hong‐Yan; Wu, Qi‐Hui; Yan, Jia‐Wei; Mao, Bing‐Wei (ChemElectroChem, 2021)
The Cover Feature shows the nucleation and growth of initial stage lithium metal deposition beneath solid‐electrolyte interphases (SEIs) with different compositions and structures formed in Py14‐based ionic liquids containing different ratios of TFSI and FSI anions. Discrepancies in nucleation density and diffusion coefficients and their relationships with overpotentials are investigated in correlation with the SEI structures. More information can be found in the Article by J.‐W. He et al.